2020
DOI: 10.5194/wcd-2020-5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The sensitivity of atmospheric blocking to changes in upstream latent heating – numerical experiments

Abstract: <p><strong>Abstract.</strong> Recent climatological studies based on trajectory calculations have pointed to an important role of latent heating during cloud formation for the dynamics of anticyclonic circulation anomalies such as atmospheric blocking. However, the causal relationship between latent heating and blocking formation has not yet been fully elucidated. To explicitly study this causal relationship, we perform sensitivity simulations of five selected blocking… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
1
6
1
Order By: Relevance
“…In Figure 12a, we see a WCB approaching the jet stream, and in Figure 12b, we observe the situation two days later. We observe a displacement of the jet stream by the WCB as Steinfeld et al (2020) found while examining the same case as shown in Figure 12. As discussed before, WCBs can influence the jet in different ways: either they lead to local wind speed maxima (jet streaks, as in Fig.…”
Section: Jet Displacementsupporting
confidence: 74%
“…In Figure 12a, we see a WCB approaching the jet stream, and in Figure 12b, we observe the situation two days later. We observe a displacement of the jet stream by the WCB as Steinfeld et al (2020) found while examining the same case as shown in Figure 12. As discussed before, WCBs can influence the jet in different ways: either they lead to local wind speed maxima (jet streaks, as in Fig.…”
Section: Jet Displacementsupporting
confidence: 74%
“…Dedicated studies involving specific processes, as performed by Steinfeld et al . (2020) for diabatic heating, are therefore recommended.…”
Section: Discussionmentioning
confidence: 99%
“…This velocity is calculated by comparing the intensity-weighted center of a 140 block at its date of onset to its date of decay and divide this distance in kilometers by the blocking duration. This method is consistent with the propagation velocity used by Steinfeld et al (2018). Blocks are categorised as winter or summer blocks based on their onset date being in respectively the months December, January or February, or June, July or August.…”
Section: D Cell-tracking Algorithmmentioning
confidence: 99%
“…For each group, the coordinates of the weighted centres of the blocks based on their BI on the fourth day of their existence is used to show where the different groups of blocks occur most. The choice of the fourth day aligns with the division made by Steinfeld et al (2018) between the onset phase (day 1 and 2) and mature phase (day 3, 4 and 5) of the block. By focusing on the fourth day, we ensure that we assess the blocks during their mature phase.…”
Section: Spatial Distribution Of Different Blocking Velocitiesmentioning
confidence: 99%
See 1 more Smart Citation